Effects of flavour variety on the intake and palatability of commercial feed in nursery pigs - Huenul, Elizabeth; Salazar, Laura; Frias, Daniela; Videka, Milivoy; Luna, Daniela; Dwyer, Dominic M.; Figueroa, Jaime (Frontiers in Veterinary Science, 2023)
Sensory-specific satiety (SSS) could negatively affect pigs' feed intake, even when diets satisfy their nutritional requirements. We evaluated the short-term effects of SSS on feed intake and palatability. Thirty-two nursery pigs (tested in pairs) were exposed to short-term feeding trials for six days. In trial 1, animals received for 90 minutes over three consecutive days three feeders: with different flavours (VAR); the same flavour (MON); or a mixture of the three flavours (MIX) in a 3x3 Latin square design. In trial 2, with the same animals and different flavours, the three feeders were delivered successively (1 feeder every 30 minutes). In trial 1, there was a day-by-diet interaction (F 4,36 = 2.98; P=0.032), where the VAR diet was least consumed on the first day but most consumed subsequently. In trial 2 a triple interaction between diet, day and delivery order modified pig`s intake (F 12,15 = 3.33; P=0.015), and consumption patterns (F 12,15 = 3.52; P=0.012); where VAR diet presented the highest values in the last delivery order on the third experimental day. Flavour variety may decrease the effect of SSS, increasing feed intake and hedonic value in nursery pigs when there was a previous experience with those flavours.